CHEVRON-TYPE HALITE AND NODULAR ANHYDRITE IN THE TRIASSIC SUBSURFACE EVAPORITES OF THE IONIAN ZONE (WESTERN GREECE) - Pomoni-Papaioannou, F.; Karakitsios, V.; Kamberis, E.; Marnelis, F. (Bulletin of the Geological Society of Greece, 2004)
Samples of the Ionian zone (western Greece) subsurface evaporites, obtained from well cores in salt bodies and in depths ranging from 1000 to 3500m, are texturally studied. Layered halite rocks consisting of chevron-type halite crystals represent most of the specimens. Between the chevron -type halite crystals, which are fluid inclusions-rich, clear halite without inclusions has been diagenetically formed by dissolution and precipitation processes. Anhydrite always accompanies the halite rocks as crystals or nodules. No-occurrence of gypsum has been detected. Along halite grain boundaries dolomite crystals occur. Dolomite grew on halite crystal surfaces as an early diagenetic mineral. Some dolomite crystals are clearly derived by replacement of anhydrite crystals. Halite layers are rich in clay and carbonaceous material favoring reducing environment (presence of pyrite crystals). Chevron-type halite supports accumulation beneath a body of brine, possibly recording annual precipitation cycles. However, its close association with nodular anhydrite cannot exclude the possibility of halite development, in a shallow-water or emergent environment by displacement from capillary brines. Since the studied halite crystals show evidence of mineral replacements and displacement, we suggest an analogous mechanism including accumulation from a standing body of brine and subsequent textural modification in the groundwater zone. Although, Ionian subsurface evaporites have undergone the above-mentioned diagenetical processes, they still reU in their primary textural characteristics. Real brecciation has not been detected in subsurface, except of an in-situ pseudo-brecciation. This observation clearly shows that the outcropping evaporite solution-collapse breccias were formed in the realm of meteoric zone, after the Ionian zone orogenesis.